Strategi Perlindungan Data dan Pengendalian Risiko Keamanan Informasi dalam Infrastruktur Digital Nasional - Windi Antika; Muhammad Irwan Padli Nasution (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The rapid advancement of information technology has fundamentally transformed how governments, businesses, and societies manage and distribute data. Digitalization of public services provides significant efficiency, yet it also introduces vulnerabilities related to information security and individual privacy. Within the context of national digital infrastructure development, cybersecurity and data protection have become critical issues that directly affect national stability, data sovereignty, and public trust in digital governance systems. This article aims to analyze data protection strategies and information security risk control mechanisms relevant to Indonesia amid the rising frequency of cyberattacks and data breaches. The research employs a qualitative descriptive approach through literature review, examining national policies, international standards such as ISO/IEC 27001 and the NIST Cybersecurity Framework, and previous studies on cybersecurity in public institutions. The findings reveal that effective data protection requires synergy among legal frameworks, implementation of advanced information security technologies, cyber risk management practices, and the enhancement of digital literacy within society. Furthermore, the establishment of integrated cybersecurity governance and cross-sector collaboration between the government, private entities, and the public is crucial for building sustainable national digital resilience. Implementing these strategies not only strengthens data security but also increases public trust and Indonesia’s competitiveness in the global digital economy.